Propulsion System Design For The Indonesian Semi High Speed Train - Shalahuddin, Lukman; Putranto, Kartiko E.; Eskayudha, Dimas B. (Majalah Ilmiah Pengkajian Industri; Journal of Industrial Research and Innovation, 2023)
This paper describes a study on the development of methodology to select the most appropriate technology, and the most optimum design and configuration for the propulsion system of the semi-high speed intercity train that will be operated on the Jakarta-Surabaya corridor. It also describes the method to calculate resistance loads Â and tractive forces and hence the power required to propel the train along the specified route within targeted time. Among the output of this study is a recommendation for the most optimum propulsion system with basic/ main parameters for main components such as diesel engine, traction motor and the possibility of Diesel Electric Multiple Unit (DEMU) Hybrid battery system.